Impact of solid residence time (SRT) on functionally relevant microbial populations and performance in full‐scale enhanced biological phosphorus removal (EBPR) systems. (14th October 2019) - Onnis‐Hayden, Annalisa; Majed, Nehreen; Li, Yueyun; Rahman, Sheikh Mokhlesur; Drury, Douglas; Risso, LeAnna; Gu, April Z.
Abstract: Investigations of the impact of solid residence time (SRT) on microbial ecology and performance of enhanced biological phosphorus removal (EBPR) process in full‐scale systems have been scarce due to the challenges in isolating and examining the SRT from other complex plant‐specific factors. This study performed a comprehensive evaluation of the influence of SRT on polyphosphate‐accumulating organisms (PAOs) and glycogen‐accumulating organisms (GAOs) dynamics and on P removal performance at Clark County Water Reclamation District Facility in Las Vegas, USA. Five parallel treatment trains with separated clarifiers were operated with five different SRTs ranging from 6 to 40 days. Microbial community analysis using multiple molecular and Raman techniques suggested that the relative abundances and diversity of PAOs and GAOs in EBPR systems are highly affected by the SRT. The resultant EBPR system stability and performance can be potentially controlled and optimized by manipulating the system SRT, and shorter SRT (<10 days) seems to be preferred. Practitioner points: Phosphorus removal performance and kinetics are highly affected by the operational solid residence time (SRT), with lower and more stable effluent P level achieved at SRT < 10 days. Excessive long SRTs above that needed for nitrification may harm EBPR performance; additionally, excessive long SRT may favor GAOs to dominate over PAOs and thus further reducing efficient use of rbCOD for EBPR. Microbial population abundance and diversity, especially those functionally relevant PAOs and GAOs, can impact the P removal performances, and they are highly dependent on the operational solid residence time. EBPR performance can be potentially controlled and optimized by manipulating the system SRT, and shorter SRT (≤10 days) seems to be preferred at the influent rbCOD/P ratio and environmental conditions as in the plant studied. Abstract : Five different Solid Residence Time (SRTs) were tested at a full scale Water Reclamation Facility (WRF) in Las Vegas, and the impact on enhanced biological phosphorus removal (EBPR) performance and on microbial population evaluated.